2019
DOI: 10.4103/jmh.jmh_135_18
|View full text |Cite|
|
Sign up to set email alerts
|

Office cervicoscopy versus stationary colposcopy in suspicious cervix: A randomized controlled trial

Abstract: Study Objective:The objective of the study was to estimate the diagnostic accuracy and doctor satisfaction of small caliber office cervicoscopy versus stationary colposcopy in diagnosis of ectocervical as well as endocervical lesions in women clinically presented with suspicious cervix.Patients and Methods:Eligible 112 cases with clinically suspicious cervix were randomized into Group A (56 cases) and Group B (56 cases) who were subjected to small caliber office cervicoscopy and stationary colposcopy, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A partial endocervical SCJ is visible using the Kogan Endo Speculum or hygroscopic dilatator [ 10 ].Furthermore, Richards et al [ 11 ] reported that the use of vaginal estrogen cream twice per week for 6 weeks for patients with smear abnormalities and a low estrogen status improved the satisfactory colposcopy rate and improved the accuracy of the prediction of true high-grade pre-invasive disease. We can also use cervicoscopy and microcolposcopy as some authors do [ 12 – 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A partial endocervical SCJ is visible using the Kogan Endo Speculum or hygroscopic dilatator [ 10 ].Furthermore, Richards et al [ 11 ] reported that the use of vaginal estrogen cream twice per week for 6 weeks for patients with smear abnormalities and a low estrogen status improved the satisfactory colposcopy rate and improved the accuracy of the prediction of true high-grade pre-invasive disease. We can also use cervicoscopy and microcolposcopy as some authors do [ 12 – 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to the current work, where, 59% of patients in the colposcopic group and 69% of patients in the office cervicoscopy group received medical attention, followed by diathermic cautery in about 26% of patients in the colposcopic group and 15% in the office cervicoscopy group. Darwish et al [11] concluded that, office cervicoscopy is a good tool for identification of cervical lesions in suspicious cervix, especially if added to stationary colposcopy. Cervicoscopy offers a better assessment of the endocervical canal due to its small caliber, especially in cases of CIN2 and CIN3 with a possibility to examine the endometrial cavity at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure and biopsy are two key steps in colposcopy. For patients with a type 3 transformation zone (TZ), some clinicians employ cervicoscopy as a supplemental imaging technique[ 2 ]. However, there were no related solutions for the dilemma caused by adhesions or obstructions.…”
Section: Introductionmentioning
confidence: 99%